2019
DOI: 10.1186/s40738-019-0063-y
|View full text |Cite
|
Sign up to set email alerts
|

IVF outcomes after hysteroscopic metroplasty in patients with T- shaped uterus

Abstract: BackgroundT- shaped uterus may be associated with infertility and adverse pregnancy outcomes. Hysteroscopic metroplasty may improve the reproductivity for these cases. To our knowledge, there is no data in literature about the clinical consequences of in vitro fertilization (IVF) in patients undergoing hysteroscopic metroplasty for T-shaped uterus. The principal objective of the current study is to assess the impact of hysteroscopic metroplasty for T-shaped uterus on the reproductive outcomes of IVF.MethodsIVF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
35
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(36 citation statements)
references
References 28 publications
0
35
0
1
Order By: Relevance
“…Since there are concerns that T‐shaped uterus may be associated with poor reproductive outcome, some authors are proposing hysteroscopic metroplasty as potential treatment for T‐shaped uterus in patients with a history of impaired reproductive outcome. Recently, a cascade of surgical reports on metroplasty of T‐shaped uterus has been published 2,123,125–130,135–137,139 (Table S2). All the studies mentioned improvement of reproductive outcome in patients with T‐shaped uterus after metroplasty: eight studies reported an increase in pregnancy rate 123,125–128,135,137,139 , seven studies reported increase in live‐birth rate 2,123,125,127,129,130,135 , five studies reported reduction in miscarriage rate 2,127–129,137 , four studies reported increased term‐delivery rate 128,135–137 and one study reported reduction in ectopic‐pregnancy rate 128 (Table 3).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Since there are concerns that T‐shaped uterus may be associated with poor reproductive outcome, some authors are proposing hysteroscopic metroplasty as potential treatment for T‐shaped uterus in patients with a history of impaired reproductive outcome. Recently, a cascade of surgical reports on metroplasty of T‐shaped uterus has been published 2,123,125–130,135–137,139 (Table S2). All the studies mentioned improvement of reproductive outcome in patients with T‐shaped uterus after metroplasty: eight studies reported an increase in pregnancy rate 123,125–128,135,137,139 , seven studies reported increase in live‐birth rate 2,123,125,127,129,130,135 , five studies reported reduction in miscarriage rate 2,127–129,137 , four studies reported increased term‐delivery rate 128,135–137 and one study reported reduction in ectopic‐pregnancy rate 128 (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, a cascade of surgical reports on metroplasty of T‐shaped uterus has been published 2,123,125–130,135–137,139 (Table S2). All the studies mentioned improvement of reproductive outcome in patients with T‐shaped uterus after metroplasty: eight studies reported an increase in pregnancy rate 123,125–128,135,137,139 , seven studies reported increase in live‐birth rate 2,123,125,127,129,130,135 , five studies reported reduction in miscarriage rate 2,127–129,137 , four studies reported increased term‐delivery rate 128,135–137 and one study reported reduction in ectopic‐pregnancy rate 128 (Table 3). After metroplasty, pregnancy rate varied between 49.6% and 88% 123,126,128,135,137,139 , clinical pregnancy rate was between 43.2% and 83.3% 123,125,127 , miscarriage rate between 7% and 49.6% 123,125,127,128,137 and live‐birth rate varied between 35.1% and 76% 2,123,125,127,129,130,135 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…antecedentes de resultados reprodutivos ruins: infertilidade(13,26,27), abortamento(20,21,(26)(27)(28), aborto de repetição(20,21,(26)(27)(28), parto pré-termo(29,30), falha de implantação(20,21,27- 29,31) e gravidez ectópica(29). Não há dados referentes a desfechos reprodutivos do útero em "T" na população geral; não se sabe, portanto, quantas mulheres conseguem alcançar gravidez bem-sucedida apesar de ter útero em "T", pois elas não chegam aos serviços de medicina reprodutiva.…”
unclassified